2020
DOI: 10.1634/theoncologist.2019-0568
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Status Quo of Physician Attire in the Palliative Care Setting

Abstract: Background, Aim, and Hypothesis This randomized controlled trial aimed to compare the impact of a physician's attire on the perceptions of patients with cancer of compassion, professionalism, and physician preference. Our hypothesis was that patients would perceive the physician with formal attire as more compassionate than the physician wearing casual attire. Materials and Methods One hundred five adult follow‐up patients with advanced cancer were randomized to watch two standardized, 3‐minute video vignettes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
(130 reference statements)
0
5
1
Order By: Relevance
“…19 Recent report by Azhar et al demonstrated patients aged less than 60 years were more likely to prefer formal attire than patients at least 60 years. 29 In the current study, there was no difference in physician attire preference among each respondent age group.…”
Section: Discussioncontrasting
confidence: 45%
“…19 Recent report by Azhar et al demonstrated patients aged less than 60 years were more likely to prefer formal attire than patients at least 60 years. 29 In the current study, there was no difference in physician attire preference among each respondent age group.…”
Section: Discussioncontrasting
confidence: 45%
“…Some studies have shown preference for different forms of attire such as scrubs (eg, specific circumstances such as gastroenterology suites18 53 and emergencies5) and informal attire,54 and some have revealed no specific patient preferences 52 55 56. Five studies noted that patient perceptions of compassion, professionalism and credibility were not associated with a physician’s dress 25 32 57–59. Finally, some studies have demonstrated that attire is more important to patients who are older,34 51 60 a finding we noted in Japan and the USA.…”
Section: Discussionmentioning
confidence: 93%
“…A survey of advanced-stage tumor patients was able to rule out a relationship between physician professionalism and compassion and professional attire [ 34 ]. Likewise, physician attire did not play a role in the perceptions of patients in a military eye clinic [ 10 ].…”
Section: Discussionmentioning
confidence: 99%